LINC00319 promotes osteosarcoma progression by regulating the miR‐455‐3p/NFIB axis. (28th July 2020) - Sun, Farui; Yu, Ziliang; Wu, Bingbing; Zhang, Haiping; Ruan, Jing
Abstract: Background: Numerous studies have shown that aberrant expression of long non‐coding RNAs (lncRNAs) is associated with the development and metastasis of osteosarcoma (OS). However, the role and function of LINC00319 with respect to regulating OS progression is unknown. The present study aimed to reveal the function and related mechanism of LINC00319 in OS. Methods: The expression of LINC00319, miR‐455‐3p and nuclear factor IB (NFIB) in OS cells and tissues was determined using a reverse transcriptase‐polymerase chain reaction (PCR). The sublocalization of LINC00319 was predicted by the lncATLAS database (http://lncatlas.crg.eu ) and RNA fluorescence in situ hybridization (FISH) was further performed to detect the subcellular localization of LINC00319. LINC00319, miR‐455‐3p and NFIB target sites were predicted by StarBase (http://starbase.sysu.edu.cn/index.php ) and validated using a dual luciferase reporter gene assay. We subsequently performed LINC00319 gain‐ and loss‐of‐function studies to define the role of LINC00319 in OS cell migration. Results: PCR results showed that lncRNA LINC00319 exhibited high expression in tumor cells and tissue. Moreover, LINC00319 was positioned in the cytoplasm, which was identified by FISH. Knockdown of lncRNA LINC00319/NFIB or overexpression of miR‐455‐3p blocked the migration of OS cells. In addition, the inhibitory effect of migration with the knockdown of lncRNA LINC00319 was partially blocked by administration of miR‐455‐3p inhibitor. Conclusions: lncRNA LINC00319 may promote OS progression by regulating the miR‐455‐3p/NFIB axis, which probably serves as an innovative potential indicator of prognosis and a target of therapy for OS. Abstract : Long non‐coding RNA LINC00319 facilitates osteosarcoma cell migration by sponging miR‐455‐3p to upregulate NFIB.